2022
DOI: 10.1029/2022jd036773
|View full text |Cite
|
Sign up to set email alerts
|

A Decomposition of the Atmospheric and Surface Contributions to the Outgoing Longwave Radiation

Abstract: The outgoing longwave radiation (OLR), which consists of the thermal radiation from both the atmosphere and surface, is of critical importance to the Earth radiation energy budget. To understand the global OLR distribution, it is important to quantify the varying atmospheric and surface contributions. In this work, we present such a quantification using radiative transfer computations based on global reanalysis atmospheric data. By dissecting the OLR simulated following the radiative transfer equation, we quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
(97 reference statements)
4
2
0
Order By: Relevance
“…Interestingly, these positive non‐cloud biases tend to be compensated by cloud biases of an opposite sign, which in some models results in a seemingly good all‐sky radiation budget (see Table 1 and Table S1 in Supporting Information ) as noted above. In addition, it is also interesting to notice that the surface temperature caused radiation biases are mostly noticeable in the Polar region, in agreement with the recognition that the atmosphere is the most transparent to surface emission in these regions (e.g., Feng et al., 2023; H. Huang & Huang, 2022). It ought to be noted that the biases in these geophysical variables can be detected by simply comparing GCM simulations to the observations, although their impacts on the radiation balance of the model would not be conveniently quantified without the aid of the kernels.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Interestingly, these positive non‐cloud biases tend to be compensated by cloud biases of an opposite sign, which in some models results in a seemingly good all‐sky radiation budget (see Table 1 and Table S1 in Supporting Information ) as noted above. In addition, it is also interesting to notice that the surface temperature caused radiation biases are mostly noticeable in the Polar region, in agreement with the recognition that the atmosphere is the most transparent to surface emission in these regions (e.g., Feng et al., 2023; H. Huang & Huang, 2022). It ought to be noted that the biases in these geophysical variables can be detected by simply comparing GCM simulations to the observations, although their impacts on the radiation balance of the model would not be conveniently quantified without the aid of the kernels.…”
Section: Resultssupporting
confidence: 78%
“…Interestingly, these positive non-cloud biases tend to be compensated by cloud biases of an opposite sign, which in some models results in a seemingly good all-sky radiation budget (see Table 1 and Table S1 in Supporting Information S1) as noted above. In addition, it is also interesting to notice that the surface temperature caused radiation biases are mostly noticeable in the Polar region, in agreement with the recognition that the atmosphere is the most transparent to surface emission in these regions (e.g., Feng et al, 2023;H. Huang & Huang, 2022).…”
Section: Tablesupporting
confidence: 75%
“…35 , evidencing that the ERA5 spectral kernels generated here capture the major spectral features of the radiative sensitivity. Moreover, the TOA kernels resemble the vertically decomposed atmospheric contribution to OLR as shown in Huang and Huang 29 , corroborating the fact that the OLR in different bands mostly originates from different vertical layers.…”
Section: Data Recordssupporting
confidence: 73%
“…A number of studies have demonstrated how climate changes can be better detected by radiation spectral changes 15 – 22 and can be attributed based on the distinctive spectral signatures of radiative forcing and feedback 19 , 23 , 24 . A growing interest especially worth noting is that in the far-infrared (FIR) spectrum, which is crucial for the Earth energy budget 25 – 29 and has motivated ongoing development of several satellites 26 – 28 . Spectrally decomposed kernels would facilitate the dissection of Earth radiation budget, including that in the FIR, and help identify the major geophysical variables accounting for the radiation variability.…”
Section: Background and Summarymentioning
confidence: 99%
“…Observations and advanced Earth system models have shown that the Earth's climate system is relatively stable, despite longwave spectra being nearly opaque (only 17% of the global‐mean surface thermal emission is transmitted through the clear‐sky atmosphere to space (Costa & Shine, 2012; Huang & Huang, 2022, Figure S1). This stability is quantified by the clear‐sky longwave feedback parameter, defined as the change in OLR per degree of surface warming.…”
Section: Introductionmentioning
confidence: 99%